Produktivitas Sapi Bali di Lahan Pastura dan Perkebunan Kelapa Sawit di Kabupaten Keerom Provinsi Papua - Kocu, O.; Salundik, Salundik; Priyanto, R.; Prihantoro, I. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
Bali cattle are potentially developed on pasture and palm oil plantation lands. They are kept in small scale by local farmers. The study aimed to investigate the forage and bali cattle productivitie in those two grazing areas. Total land area, carrying capacity and total land capacity for bali cattle were analysed to evaluate the forage productivity of pasture and oil plantation grazing areas. A total of 60 heads of bali cattle aging 1-3 years were used to evaluate their productivities including bodyweight and linear body measurements. A number of 30 heads of the animal had been raised on pasture and the other 30 heads on palm oil plantation. The results showed that there were 7191 ha of pasture and 5519 ha of palm oil plantation that could cover grazing cattle of 28 188.72 animal unit and 20 585.87 animal unit respectively. The carrying capacity of pasture was slightly higher than that of palm oil plantation, which were 3.92 AU and 3.73 AU per ha per year respectively. The bali cattle, particularly female animal, raised on pasture had better productivity in term of body weight and hip height. The higher cattle productivity on pasture was due to the additional supplementation of King grass and Elephant grass. In general, the bali cattle kept in the two different raising system (pasture and palm oil plantation system) had good performance since their population were still below their carrying capacities.